Boutique effluent colour treatment using dead fungal biomass - Mamun, Abdullah Al; Mohammad, Zahangir Alam; Mohamad, Marzuki; Mustapha, Mujeli (Universiti Tenaga Nasional, 2022)
The boutique industry has long become a cultural heritage of Malaysia, but the dyed effluents discharged into the water bodies were outrageous. This study assessed the potential of dead microorganism biosolids to treat the Boutique industry effluent. Therefore, the primary goal of this paper is to prepare an adsorbent using dead fungal biomass and evaluate its adsorption ability in removing colours from dye wastewater. The majority of a fungus strain in the wasted biomass used in producing the adsorbent is Phanerochaete chrysosporium. A feasibility study was done using Methylene-blue and Eriochrome black solutions as synthetic wastewater to examine the efficacy of the adsorbent. The optimization study was conducted on real boutique wastewater collected from Kelantan. Lastly, the colour removal efficiency as a function of process variables; biomass concentration, contact time, initial pH, and agitation speed was studied using five levels of central composite design and response surface methodology procedures. A good representable quadratic model was developed and optimized using the experimental data, and the best colour removal of about 93% was achieved according to the following process conditions; biomass concentration of 0.5 g/L, the processing time of 2 hours, initial pH of 8, and agitation speed of 200 rpm. The results demonstrated that the dead microorganism biomass would treat wastewater generated from the boutique industries